2020
DOI: 10.1016/j.mayocp.2019.10.008
|View full text |Cite
|
Sign up to set email alerts
|

CELLTOP Clinical Trial: First Report From a Phase 1 Trial of Autologous Adipose Tissue–Derived Mesenchymal Stem Cells in the Treatment of Paralysis Due to Traumatic Spinal Cord Injury

Abstract: Spinal cord injury (SCI) is a devastating condition with limited pharmacological treatment options to restore function. Regenerative approaches have recently attracted interest as an adjuvant to current standard of care. Adipose tissueederived (AD) mesenchymal stem cells (MSCs) represent a readily accessible cell source with high proliferative capacity. The CELLTOP study, an ongoing multidisciplinary phase 1 clinical trial conducted at Mayo Clinic (ClinicalTrials.gov Identifier: NCT03308565), is investigating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(50 citation statements)
references
References 20 publications
1
49
0
Order By: Relevance
“…This safety profile is consistent with the experience of other human clinical trials involving MSC therapy. 33,[37][38][39][40][41][42][43] The potential efficacy of MSC therapy for ARDS in COVID- Findings from this study also suggest the impact of MSC therapy on important immunologic and inflammatory processes that lead to organ injury in COVID-19-infected patients. Cytokine release syndrome is a major underlying pathophysiological process in ARDS and was found to decrease with MSC therapy in seven of the studies analyzed.…”
Section: Inflammatory Cytokinesmentioning
confidence: 61%
See 1 more Smart Citation
“…This safety profile is consistent with the experience of other human clinical trials involving MSC therapy. 33,[37][38][39][40][41][42][43] The potential efficacy of MSC therapy for ARDS in COVID- Findings from this study also suggest the impact of MSC therapy on important immunologic and inflammatory processes that lead to organ injury in COVID-19-infected patients. Cytokine release syndrome is a major underlying pathophysiological process in ARDS and was found to decrease with MSC therapy in seven of the studies analyzed.…”
Section: Inflammatory Cytokinesmentioning
confidence: 61%
“…These showed clear decreases in pro-inflammatory cytokines, including IL-1, IL-6, TNF-α, and CRP, and increased lymphocytes and IL-10 within 5 days of MSC therapy (Table 5), [20][21][22]24,25,28 which supported an immunomodulatory effect of the MSC therapy. clinical studies have demonstrated that MSC therapy is safe and has the potential to mitigate inflammatory and physiologic damage for a variety of conditions involving the central nervous, 32,33 cardiac, 34,35 renal, 36 gastrointestinal, [37][38][39] and respiratory 40,41 systems. Our analysis of the literature suggests similar results for MSC therapy for treating ARDS in COVID-19 patients.…”
Section: Inflammatory Cytokinesmentioning
confidence: 99%
“…Despite promising results obtained with preclinical studies, there are still very few reports in the available literature describing successful application of ADSCs for SCI treatment in clinical trials. However, Bydon et al 26 published the outcomes obtained with an ongoing phase 1 clinical trial conducted at Mayo Clinic ( ClinicalTrials.gov Identifier: NCT03308565) 27 . The mentioned case report describes the ADSC-based therapy of paralysis after traumatic SCI.…”
Section: Discussionmentioning
confidence: 99%
“…However, MRI examination indicated that the lesion size remained unchanged. In a recent paper, Bydon et al [ 65 ] reported the treatment of a SCI patient with 100 million autologous ADSCs. The cells were administered intrathecally.…”
Section: Mesenchymal Stem Cell Therapy For Spinal Cord Injurymentioning
confidence: 99%